2010
DOI: 10.1111/j.1469-8137.2010.03338.x
|View full text |Cite
|
Sign up to set email alerts
|

A depth‐controlled tracer technique measures vertical, horizontal and temporal patterns of water use by trees and grasses in a subtropical savanna

Abstract: Summary• As described in the two-layer hypothesis, woody plants are often assumed to use deep soils to avoid competition with grasses. Yet the direct measurements of root activity needed to test this hypothesis are rare.• Here, we injected deuterated water into four soil depths, at four times of year, to measure the vertical and horizontal location of water uptake by trees and grasses in a mesic savanna in Kruger National Park, South Africa.• Trees absorbed 24, 59, 14 and 4% of tracer from the 5, 20, 50, and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
159
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(169 citation statements)
references
References 58 publications
8
159
1
1
Order By: Relevance
“…The source-water partitioning between C. drummondii and A. gerardii is consistent with a large number of studies that have found a vertical separation of tree and grass root systems (Jackson et al 1996, Weltzin andMcPherson 1997, but see Scholes and Archer 1997, Bond 2008, Kulmatiski et al 2010. However, it is surprising that C. drummondii clones measured in the grassland matrix were accessing the same soil water source as the mature shrubs, even up to 5 m from the center of the shrub island ( p .…”
Section: Discussionsupporting
confidence: 86%
“…The source-water partitioning between C. drummondii and A. gerardii is consistent with a large number of studies that have found a vertical separation of tree and grass root systems (Jackson et al 1996, Weltzin andMcPherson 1997, but see Scholes and Archer 1997, Bond 2008, Kulmatiski et al 2010. However, it is surprising that C. drummondii clones measured in the grassland matrix were accessing the same soil water source as the mature shrubs, even up to 5 m from the center of the shrub island ( p .…”
Section: Discussionsupporting
confidence: 86%
“…tree sites). This observation clearly contradicts the widely discussed two-layer hypothesis, proposing independent ecological niches for root water uptake of trees and understorey plants in savannahs in order to avoid competition (Hipondoka et al, 2003;Holdo and Planque, 2013;Kulmatiski et al, 2010;Walter et al, 1971). Moreover, exponential soil profiles of plant available nitrogen cause a coupled water and nutrient competition between herbs and trees in this ecosystem during spring (Dubbert et al, 2014b).…”
Section: Dynamic Responses Of Event Water Use and Plasticity Of Watermentioning
confidence: 59%
“…1a), and that deep soil layers retain soil moisture for a significant proportion of the growing season. Previous work using tracers has revealed that trees and grasses differ (clearly but subtly) in terms of functional rooting depth in a similar site in nearby Kruger National Park (Kulmatiski et al 2010, Kulmatiski andBeard 2013a). These authors also found that trees (but not grasses) appear to be highly plastic in their uptake patterns, using shallow soil moisture early in the season and shifting to sources below 30 cm depth later in the season (Kulmatiski and Beard 2013a).…”
Section: Discussionmentioning
confidence: 84%